Synthesis of Biodiesel from Kesambi Oil using Indigenous Lipase - Ledo, Mellisa E.S.; Nitsae, Merpiseldin; Solle, Hartini R.L. (SCISCITATIO, 2020)
Kesambi (Schleichera oleosa L.) is one of ligneous tree that is abundantly found in Timor island, East Nusa Tenggara Province of Indonesia. Kesambi is known as an important component in local smoked meat home industry. Kesambi is also a promising natural source for the production of biodiesel. Application of three lipolytic fungi that is isolated from kesambi seeds and the use kesambi seeds flour as medium for indigenous lipase synthesis (Aspergillus niger M1407 lipase) by Solid-State Fermentation (SSF) showed good result for lipase and biodiesel industry development. This study aimed to characterize biodiesel synthesis using indigenous lipase from kesambi seeds. Experiments were carried out through five stages namely: oil extraction from kesambi seeds, purification of kesambi oil (degumming), extraction of A. niger M1407 lipase, trans-esterification and esterification activity of A. niger M1407 lipase assay and characterization of biodiesel. Biodiesel synthesis using A. niger M1407 lipase through esterification reaction produced biodiesel with an average acid number of 0.33 and 0.40 mg/g, water content 9.52 % and 10.47 % and density 0.7 g/mL. Biodiesel obtained from kesambi oil has lower acid numbers and densities but higher water content compared to Indonesian National Standard (SNI) value. Optimalization of the biodiesel kesambi oil synthesis could be done through adjusting ethanol and kesambi oil ratio and also by reducing water as a by-product of esterification reaction